Assessment of Ichu fibers as non-expensive thermal insulation system for the Andean regions - Noel, Julien George Andre (2015)
In the Andean regions, low temperatures (5 to −25 °C) combined with the wind effect give the sensation of extreme cold. Besides, in the rural areas, dwelling structures are very rudimentary, being based on adobe walls and galvanized steel corrugated roofs. The combination of weather issues and construction without thermal insulation considerations put people in extreme living conditions. Using local and cheap natural fibers as thermal insulation is a great alternative especially to upgrade/refurbish rudimentary constructions. In areas above 3000 m over sea level, natural fibers are vast and cheap (∼0.15 USD/kg), especially fibers named “Ichu”. In this study thermal properties of natural fibers were characterized according to the ASTM C177. Results show that the thermal conductivity varies from 0.047 to 0.113 W/m K, for mats with unidirectional oriented fibers, being fine Ichu which have the lowest values. For the fine Ichu fiber to be competitive in terms of cost per unit thermal resistance, fiber mat density were reduced, arranging the fibers randomly; results show a significant reduction in density, without increasing significantly the thermal conductivity. According to these results Ichu fibers have exceptional thermal insulation properties. Moreover, this is the first conducted study on the thermal performance of this natural Andeans fiber.